Citizens of Empire: Education and Teacher Exchanges in Canada and the Commonwealth, 1910–40. Issue 4 (4th July 2017) - Bryce, Benjamin
ABSTRACT: This article examines how one group of actors actively infused education, citizenship and Canada's international relationships with a sense of empire in the first third of the twentieth century. Making use of archival and published sources from collections in Canada and Britain, it focuses in particular on imperial citizenship teaching in Canadian schools, a number of education conferences held in the United Kingdom and the exchanges of elementary and high school teachers and school inspectors between commonwealth countries. In this period, politicians and bureaucrats in Canada and other dominions actively connected their education systems to an imperial network at the very moment that others were striving to attain more economic and political autonomy from the British government. Education came to occupy a significant cultural space alongside the trade agreements and constitutional changes that slowly recalibrated the nature of the British imperial system in the interwar period. Imperial education projects were an important feature of the cultural politics of a fading empire, but they were driven by actors in both the imperial centre and the self-governing dominions. This article argues that between 1910 and 1940 teachers and politicians in Canada drew on an international support network, actively fostered new ideas of citizenship, and strove to assert the country's belonging in the British Empire.